PENGUATAN WOMENPRENEUR DALAM PENINGKATAN PENDAPATAN PEREMPUAN PADA KELOMPOK UMKM SAMBAL DAN LAUK KEMASAN KHAS RIAU - Berampu, Lailan Tawila; Utami, Bunga Chintia; Siregar, Taufik; Khoiriyah, Mayla (Universitas Mataram, 2025)
The number of formal employment sectors available in Indonesia is very limited so the employment participation rate is not proportional to the available jobs. This causes the unemployment rate to increase, which has an impact on the increase in poverty rates. To encourage economic growth and reduce poverty levels, the government encourages people to work in the self-employed sector. The non-formal sector that is strongly encouraged by the current government is MSMEs. Based on data from the Ministry of Entrepreneurship and Cooperatives, in 2024 the number of micro business ownership and management will be dominated by women at 64%. This figure shows that women have a dual role in addition to being housewives, women also play a role as a booster of the ladder economy. Therefore, this paper aims to increase women's income as entrepreneurs through several trainings, especially in the fish processing business. The sampling method of this study is a census, where all members of the group of 10 people receive training. This research was conducted for 5 months (July-November 2024). The training and assistance carried out includes 4 (four) types of activities with the following results: (1) MSME actors have been able to make profit and loss statements and cash flow statements, so that business actors can separate business capital and personal finance. (2) MSME actors can explore creative ideas in design so that the appearance of MSME product packaging becomes more attractive. (3) MSME actors already have social media to help market their products, in this case the social media is Instagram (4) The technology that seeks to help MSME actors extend the product expiration period is a retorch machine.